Ligand and solvent effects in the formation and self-assembly of a metallosupramolecular cage. (11th January 2017) - Adarsh, N. N.; Chakraborty, Amarnath; Tarrés, Màrius; Dey, Surjendu; Novio, Fernando; Chattopadhyay, Basab; Ribas, Xavi; Ruiz-Molina, Daniel
Abstract : A metallosupramolecular cage and a one-dimensional coordination polymer have been synthesized and structurally characterized by single crystal X-ray diffraction. Abstract : Two bis-pyridyl-bis-urea ligands namely N, N ′-bis-(3-pyridyl)diphenylmethylene-bis-urea (L1 ) and N, N ′-bis-(3-picolyl)diphenylmethylene-bis-urea (L2 ) have been reacted with a Cu(ii ) salt resulting in the formation of a metallosupramolecular cage [{Cu2 (μ-L1 )4 (DMSO)2 (H2 O)2 }·SO4 ·X] (1 ) and a one-dimensional coordination polymer [{Cu(1)(μ-L2 )2 (H2 O)2 }{Cu(2)(μ-L2 )2 (H2 O)2 }·2SO4 ·9H2 O·X] n (2 ) (where DMSO = dimethylsulfoxide, and X = disordered lattice included solvent molecules), respectively. The single crystal structures of1 and2 are discussed in the context of the effect of the ligands, particularly the hydrogen bonding functionality of the ligand, on the supramolecular structural diversities observed in these metal organic compounds. The supramolecular packing of1 is clearly influenced by the nature of the solvent and ligand used; mixtures of DMSO/MeOH or DMSO/H2 O lead to the formation of blue crystals or a hydrogel, respectively.